Descolonização do currículo: a questão racial na formação acadêmica do assistente social - Vassalo, Verônica Gomes (2019)
The present work is the result of questions about the absence of incorporation of the Racial Question in Social Work and the importance of this issue in the Social Worker Training. Its objective is to understand the distance between class and race in the academic formation and its consequences for the professional practice of the Social Worker. We start from the assumption that the Racial Question in the professional formation in Social Work does not constitute, until the moment, significant matter to the detriment of a culture and studies based on Eurocentric tendencies. It is important to ask for this absence, to understand the impacts of this gap in the life of the black population and to question how the invisibility of this issue can have repercussions on the professional practice of the social worker. This study crosses the Brazilian Social Question, originating in the history of Brazil and the colonial / enslaved heritage, which establishes a social structure based on racialization, materializing in all social relations. The absence of the Racial Question in our school and academic trajectory is the historical result of a colonial-slave model that legitimizes an educational model that adopts Eurocentric tendencies as universal. The study is documentary, reflective, critical and proposes to identify the practices, discussions and debates of the profession; the research proposal consists of analyzing the Racial Question in the academic training of the Social Worker, understanding the influence of colonization on Brazilian society and its intersection with the Racial Question